2022
DOI: 10.3390/geosciences12030126
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Gold Alloys during Crustal Differentiation of Convergent Zone Magmas: Constraints from an AU-Rich Websterite in the Stanovoy Suture Zone (Russian Far East)

Abstract: Gold is typically transported by mafic and evolved magmas into the upper crust to be deposited in shallow oxidized porphyry and epithermal environments. However, the magmatic behavior of gold is still poorly understood and warrants further attention. Additional insights into the magmatic evolution of gold and other noble metals can be provided by investigations of primitive convergent zone magmas and products of their differentiation that contain primary-textured Au-alloys. One of the best examples of such Au-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(43 citation statements)
references
References 89 publications
0
10
0
11
Order By: Relevance
“…In addition to the above listed standards, geochemical reference samples BHVO-2 (USGS; Hawaiian basalt) and JB-3 (Geological Survey of Japan; Fuji basalt), along with Perkin Elmer standard solutions PE# N9300231-9300234 for internal calibration, were used to control the accuracy of analytical measurements. In the course of this study, the accuracy was ± 5% for trace element abundances of >20 ppm and ± 10% for chemical elements with abundances of <20 ppm [39]. Platinum-group elements (Ru, Rh, Ir, Pd, Pt) and Au were determined by ICP-MS after separation and pre-concentration by Na 2 O 2 fire-assay and tellurium co-precipitation following the method described in [40].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the above listed standards, geochemical reference samples BHVO-2 (USGS; Hawaiian basalt) and JB-3 (Geological Survey of Japan; Fuji basalt), along with Perkin Elmer standard solutions PE# N9300231-9300234 for internal calibration, were used to control the accuracy of analytical measurements. In the course of this study, the accuracy was ± 5% for trace element abundances of >20 ppm and ± 10% for chemical elements with abundances of <20 ppm [39]. Platinum-group elements (Ru, Rh, Ir, Pd, Pt) and Au were determined by ICP-MS after separation and pre-concentration by Na 2 O 2 fire-assay and tellurium co-precipitation following the method described in [40].…”
Section: Methodsmentioning
confidence: 99%
“…Platinum-group elements (Ru, Rh, Ir, Pd, Pt) and Au were determined by ICP-MS after separation and pre-concentration by Na 2 O 2 fire-assay and tellurium co-precipitation following the method described in [40]. Additional details of the analytical procedures used in the current study can be found in [39,41].…”
Section: Methodsmentioning
confidence: 99%
“…Ильдеусский интрузивный массив, расположенный в центре Брянтинского тектонического блока Станового пояса, является частью разветвленной глубинной магматогенной структуры, которая вместе с массивами Луча, Утанак и Габбровый представляет нижнекоровые горизонты крупного мезозойского островодужного сооружения [38,53]. Массивы объединены в единую магматическую систему дайкообразными подводящими каналами, ярко выражающимися в региональном магнитном поле [53].…”
Section: глубинные магматогенные системы островодужного этапа эволюци...unclassified
“…Детальные геолого-минералогические исследования Ильдеусского ультраосновного массива (Становой мобильный пояс, Дальний Восток России) показали присутствие в нем сложной сульфидной-сульфосольной минерализации цветных (медь, кобальт, никель, в подчиненом количестве цинк и свинец) и благородных (золото, серебро, платина, палладий) металлов. При этом в ассоциации с Ni-Cu-Fe сульфидами (пирротин, пентландит, кобальтистый пентландит, никелистые пирит и сфалерит, борнит, халькопирит, хизлевудит, дигенит), а также первично-магматическими (оливин, орто-и клинопироксены) и вторичными (серпентин, хлорит, тремолит, тальк) породообразующими силикатами присутствуют разнообразные сплавы Au, Cu, Ag, Ni, Zn, Sn, Pb и Sb, платиноидов (Fe-Pt, Ni-Rh-Pt, Pd-Pt), а также самородные Pt, W, Bi, Zn, Pb, Au и Ag [38,53]. Показано, что образование этих экзотических минеральных ассоциаций происходило в результате сложного и длительного (порядка 100 Ма, по [53]) взаимодействия магматических и метасоматических процессов, при этом благороднометалльная минерализация проявилась как на островодужной магматической стадии становления этой рудно-магматической системы, так и во время низкотемпературного постмагматического взаимодействия Ильдеусского массива с гидротермальными флюидами на коллизионном и постколлизионном этапах эволюции Станового пояса [38].…”
Section: Introductionunclassified
See 1 more Smart Citation